Within-Household Transmission and Bacterial Diversity of Staphylococcus pseudintermedius - Alice Wegener; Birgitta Duim; Linda van der Graaf-van Bloois; Aldert L. Zomer; Caroline E. Visser; Mirlin Spaninks; Arjen J. Timmerman; Jaap A. Wagenaar; Els M. Broens (Pathogens, 2022)
Staphylococcus pseudintermedius can be transmitted between dogs and their owners and can cause opportunistic infections in humans. Whole genome sequencing was applied to identify the relatedness between isolates from human infections and isolates from dogs in the same households. Genome SNP diversity and distribution of plasmids and antimicrobial resistance genes identified related and unrelated isolates in both households. Our study shows that within-host bacterial diversity is present in S. pseudintermedius, demonstrating that multiple isolates from each host should preferably be sequenced to study transmission dynamics.